Semantic Web Techniques for Clinical Topic Detection in Health Care - Raman, R.; Sahayaraj, Kishore Anthuvan; Soni, Mukesh; Nayak, Nihar Ranjan; Govindaraj, Ramya; Singh, Nikhil Kumar (Computer Assisted Methods in Engineering and Science; Vol 31 No 2 (2024), 2024)
The scope of this paper is that it investigates and proposes a new clustering method that takes into account the timing characteristics of frequently used feature words and the semantic similarity of microblog short texts as well as designing and implementing microblog topic detection and detection based on clustering results. The aim of the proposed research is to provide a new cluster overlap reduction method based on the divisions of semantic memberships to solve limited semantic expression and diversify short microblog contents. First, by defining the time-series frequent word set of the microblog text, a feature word selection method for hot topics is given; then, for the existence of initial clusters, according to the time-series recurring feature word set, to obtain the initial clustering of the microblog.